Intermittent Glucocorticoid Dosing Improves Muscle Repair and Function in Mice with Limb-Girdle Muscular Dystrophy - Quattrocelli, Mattia (Am J Pathol, 2017)
The muscular dystrophies are genetically diverse. Shared pathological features among muscular dystrophies include breakdown, or loss of muscle, and accompanying fibrotic replacement. Novel strategies are needed to enhance muscle repair and function and to slow this pathological remodeling. Glucocorticoid steroids, like prednisone, are known to delay loss of ambulation in patients with Duchenne muscular dystrophy but are accompanied by prominent adverse effects. However, less is known about the effects of steroid administration in other types of muscular dystrophies, including limb-girdle muscular dystrophies (LGMDs). LGMD 2B is caused by loss of dysferlin, a membrane repair protein, and LGMD 2C is caused by loss of the dystrophin-associated protein, γ-sarcoglycan. Herein, we assessed the efficacy of steroid dosing on sarcolemmal repair, muscle function, histopathology, and the regenerative capacity of primary muscle cells. We found that in murine models of LGMD 2B and 2C, daily prednisone dosing reduced muscle damage and fibroinflammatory infiltration. However, daily prednisone dosing also correlated with increased muscle adipogenesis and atrophic remodeling. Conversely, intermittent dosing of prednisone, provided once weekly, enhanced muscle repair and did not induce atrophy or adipogenesis, and was associated with improved muscle function. These data indicate that dosing frequency of glucocorticoid steroids affects muscle remodeling in non-Duchenne muscular dystrophies, suggesting a positive outcome associated with intermittent steroid dosing in LGMD 2B and 2C muscle.